Doped trimanganese tetraoxide, preparation method thereof, positive electrode material and lithium ion battery

CN117623392BActive Publication Date: 2026-10-20CNGR ADVANCED MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311566473.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-22
Publication Date
2026-10-20
Estimated Expiration
2043-11-22

AI Technical Summary

Technical Problem

但是,锰酸锂仍存在不足之处,需要进行改进

Benefits of technology

[0044]1.本申请提供的掺杂四氧化三锰二次颗粒切面存在具有多条与表面连通的缝,有利于电解液的渗入和反应,提高电子传导速率,提升充放电容量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117623392B_ABST
    Figure CN117623392B_ABST
Patent Text Reader

Abstract

The application provides a kind of doped trimanganese tetraoxide and its preparation method, positive electrode material and lithium ion battery, it relates to new energy technical field.The secondary particle of the doped trimanganese tetraoxide has multiple seams communicating with surface.The preparation method of the doped trimanganese tetraoxide includes: continuously into the mixed salt solution containing manganese and doping element, precipitant, complexing agent and oxidizing agent in the reaction kettle bottom liquid, control pH, temperature, stirring speed, feed flow rate, complexing agent concentration, carry out coprecipitation reaction to obtain trimanganese tetraoxide;The complexing agent is ammonium salt or ammonia water.The secondary particle of the doped trimanganese tetraoxide has multiple seams communicating with surface, which is beneficial to the infiltration of electrolyte, improves the electron conduction rate, improves the charge and discharge capacity, improves the cycle stability of the positive electrode material, prevents the preferential formation of crystal structure collapse during high-voltage charge and discharge process, which seriously affects the battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of new energy technology, and in particular to doped manganese tetroxide and its preparation method, cathode materials and lithium-ion batteries. Background Technology

[0002] Among current lithium-ion battery cathode materials, lithium manganese oxide, due to its abundant Mn element reserves, has advantages such as low price and simple production process. As a supplement to ternary lithium batteries, it has gradually begun to be used in price-sensitive energy storage fields and low-to-mid-range power battery fields, and has great application prospects.

[0003] Currently, traditional lithium manganese oxide materials use MnO2 as the manganese source. However, using MnO2 as the manganese source has drawbacks such as high impurity content, poor particle morphology, numerous microparticles, and a large specific surface area, which affect the electrochemical performance of lithium manganese oxide and limit its further development. Since the spinel structure of Mn3O4 is closer to that of lithium manganese oxide than that of MnO2, and there is no drastic crystal structure transformation during preparation, lithium manganese oxide materials prepared using Mn3O4 as the manganese source exhibit better performance in terms of capacity and cycle life. However, lithium manganese oxide still has shortcomings and needs improvement. Summary of the Invention

[0004] The purpose of this application is to provide a doped manganese tetroxide, its preparation method, a cathode material, and a lithium-ion battery to solve the above-mentioned problems.

[0005] To achieve the above objectives, the first aspect of this application provides a doped manganese tetroxide, wherein the doped manganese tetroxide comprises secondary particles composed of a plurality of primary particles, and the secondary particles include a plurality of slits communicating with the surface of the secondary particles.

[0006] Optionally, the doped manganese tetroxide satisfies at least one of the following conditions:

[0007] (1) The seam communicating with the surface of the secondary particles is a straight seam or a near-straight seam;

[0008] (2) The secondary particle includes a core and a shell covering the core, and the seam communicating with the surface of the secondary particle is located in the shell;

[0009] (3) The secondary particle surface includes a plurality of holes and / or slits communicating with the secondary particle surface.

[0010] Optionally, the doped manganese tetroxide satisfies at least one of the following conditions:

[0011] (1) In the secondary particle cross section, multiple slits intersect; optionally, the multiple slits are arranged in a tree-like pattern in the secondary particle cross section;

[0012] (2) The maximum length of the slit on the surface of the secondary particles is >0.6μm;

[0013] (3) The ratio of the maximum depth of the slit in the secondary particle cut surface to the diameter of the secondary particle is >10%;

[0014] Optionally, the secondary particle comprises a core and a shell covering the core, and satisfies at least one of the following conditions:

[0015] (1) The core porosity is less than the outer shell porosity;

[0016] (2) The diameter of the core is 6-10 μm; the thickness of the outer shell is 0.5-4 μm;

[0017] (3) The overall porosity of the doped manganese tetroxide is 10-30%.

[0018] Optionally, manganese tetroxide satisfies at least one of the following conditions:

[0019] a. The particle size D50 of the doped manganese tetroxide is 8μm-15μm;

[0020] b. The particle size distribution of the doped manganese tetroxide, Span = (D90 - D10) / D50, is 0.35-0.65;

[0021] c. The specific surface area of ​​the doped manganese tetroxide is 1-3 m². 2 / g;

[0022] d. The tap density of the doped manganese tetroxide is 2.4-3.0 g / cm³. 3 ;

[0023] e. The molecular formula of the doped manganese tetroxide is Mn 3-x M x O4, where 0 < x ≤ 0.3, and M is Al;

[0024] f. The molecular formula of the doped manganese tetroxide is Mn 3-x M x O4, where 0 < x ≤ 0.3, M includes Al, and M also includes one or more of B, Ni, Mg, Ti, Zr, and La.

[0025] A second aspect of this application also provides a method for preparing doped manganese tetroxide, comprising:

[0026] A mixed salt solution containing manganese and dopant elements, a precipitant, a complexing agent, and an oxidant are introduced into the bottom liquid of the reaction vessel to carry out a coprecipitation reaction. The pH value, temperature, and stirring speed in the coprecipitation reaction are controlled. After the coprecipitation reaction is completed, manganese tetroxide is obtained. The complexing agent is an ammonium salt or ammonia water.

[0027] Optionally, the preparation method satisfies at least one of the following conditions:

[0028] A. The mixed salt solution comprises a soluble manganese salt and a soluble dopant element source;

[0029] B. The soluble manganese salt is selected from one or more of MnCl2, MnSO4, and MnNO3, and the concentration of manganese ions in the soluble manganese salt is 1-5 mol / L;

[0030] C. The doping element in the soluble doping element source includes one or more of Al, B, Ni, Mg, Ti, Zr, and La, and the soluble doping element source is selected from one or more of sulfate, chloride, nitrate, boric acid, and borate. The sum of the concentrations of each doping element ion in the mixed salt solution is 0.02 to 0.2 mol / L.

[0031] D. The base liquid includes one or more of pure water, ammonia water, and sodium hydroxide solution;

[0032] E. The precipitant is a sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is 10% to 35%;

[0033] F. The complexing agent is one or more of ammonium sulfate, ammonia, ammonium nitrate, and ammonium chloride;

[0034] G. The oxidant is one or more of hydrogen peroxide, compressed air, ozone, oxygen, sodium hypochlorite, ammonium persulfate, and sodium thiosulfate.

[0035] Optionally, the preparation method satisfies at least one of the following conditions:

[0036] 1) Control the pH to 8.0–10.0 during the coprecipitation reaction;

[0037] 2) The concentration of the complexing agent during the co-precipitation reaction is controlled to be 0.5-8 g / L;

[0038] 3) Control the temperature during the co-precipitation reaction to be 40–80℃;

[0039] 4) Control the stirring speed during the coprecipitation reaction to be 400–800 rpm;

[0040] 5) Control the feed flow rate of the mixed salt solution during the co-precipitation reaction to 1.2-6% / h of the available volume of the reactor; when the oxidant is prepared as an oxidant solution, control the feed flow rate of the oxidant solution to 0.3-6% / h of the available volume of the reactor; when the oxidant is a gaseous oxidant, control the feed flow rate of the gaseous oxidant to 90-700% / h of the available volume of the reactor.

[0041] A third aspect of this application also provides a cathode material, the raw material of which includes the aforementioned doped manganese tetroxide.

[0042] The fourth aspect of this application also provides a lithium-ion battery, the raw materials of which include the above-mentioned positive electrode material.

[0043] Compared with the prior art, the beneficial effects of this application include:

[0044] 1. The secondary manganese tetroxide particles provided in this application have multiple slits connected to the surface on their cross-section, which is beneficial for electrolyte penetration and reaction, improves electron conduction rate, and enhances charge and discharge capacity.

[0045] 2. The preparation of doped manganese tetroxide provided in this application uses a co-precipitation process. By doping and adjusting parameters such as stirring speed, temperature, and pH, gaps are created in the secondary spherical cross-section, and uniform precipitation of various doping elements such as aluminum is achieved. This is beneficial to improving the cycle stability of the cathode material and preventing the preferential formation of crystal structure collapse during high-voltage charging and discharging, which would seriously affect battery performance.

[0046] 3. The cathode material prepared by doping manganese tetroxide provided in this application has high tap density and good doping uniformity, and the resulting material has a stable crystal structure, which can effectively improve the cycle performance and charge / discharge capacity of the battery.

[0047] 4. The lithium-ion battery provided in this application has good cycle stability and high charge / discharge capacity. Attached Figure Description

[0048] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0049] Figure 1 The images show a surface SEM image (left) and a magnified partial surface SEM image (right) of the precursor obtained in Example 1.

[0050] Figure 2 The images show a cross-sectional SEM image (left) and a magnified partial cross-sectional SEM image (right) of the precursor obtained in Example 1.

[0051] Figure 3 The images show a surface SEM image (left) and a magnified partial surface SEM image (right) of the cathode material obtained in Example 1.

[0052] Figure 4 The images show a surface SEM image (left) and a magnified partial surface SEM image (right) of the precursor obtained in Example 2.

[0053] Figure 5 The images show a surface SEM image (left) and a magnified partial surface SEM image (right) of the precursor obtained in Example 3.

[0054] Figure 6 Here is a cross-sectional SEM image of the precursor obtained in Example 3;

[0055] Figure 7 The images show a surface SEM image (left) and a magnified partial surface SEM image (right) of the precursor obtained in Example 4.

[0056] Figure 8 The images show the surface SEM image (left) and the magnified surface SEM image (right) of the precursor obtained in Comparative Example 1.

[0057] Figure 9 Here is a cross-sectional SEM image of the precursor obtained in Comparative Example 1;

[0058] Figure 10 The images show the surface SEM image (left) and the magnified surface SEM image (right) of the precursor obtained in Comparative Example 2.

[0059] Figure 11 Here is a cross-sectional SEM image of the precursor obtained in Comparative Example 2;

[0060] Figure 12 The images show SEM images of the precursor surface (left) and a magnified SEM image of a portion of the surface (right) obtained in Comparative Example 3.

[0061] Figure 13 The images show SEM images of the precursor surface (left) and a magnified SEM image of a portion of the surface (right) obtained in Comparative Example 4.

[0062] Figure 14 Here is a cross-sectional SEM image of the precursor obtained in Comparative Example 4;

[0063] Figure 15 Battery capacity diagrams for the cathode materials prepared from the precursors of Examples 1-4 and Comparative Examples 1-4. Detailed Implementation

[0064] It should be understood that the specific embodiments given herein are for the purpose of explaining to those skilled in the art and are exemplary only, not restrictive.

[0065] In the following description, numerous specific details are set forth to provide a thorough understanding of the invention. However, it will be apparent to those skilled in the art that the specific details are not required to practice the invention. In other instances, well-known steps or operations have not been described in detail to avoid obscuring the invention.

[0066] In this invention, "multiple" refers to three or more.

[0067] This invention provides a doped manganese tetroxide, wherein the doped manganese tetroxide comprises secondary particles composed of multiple primary particles, and the secondary particles include multiple slits communicating with the surface of the secondary particles.

[0068] Studies have shown that doping lithium manganese oxide materials with elements such as aluminum can improve material properties. For example, doping with aluminum can enhance the stability of the material structure, suppress the Jahn-Teller effect, and thus improve the high-temperature cycling performance of lithium manganese oxide materials. Currently, industrial doping involves mixing manganese and lithium sources while adding other element sources; however, this method makes it difficult to ensure the uniformity of the mixture. This application improves doping uniformity by doping the precursor. Furthermore, the presence of the aforementioned gaps facilitates electrolyte penetration, increases electron conduction rate, and enhances charge and discharge capacity.

[0069] The cross-section testing method of this invention is as follows: the cross-section is obtained by cutting the powder-particle sample of this invention with an ion beam, and then photographed with an electron microscope to obtain a cross-section SEM image.

[0070] Determination of the slit in the cut surface: Considering that the slit in the cut surface of this invention is very narrow, it may be partially obscured when the powder or particulate sample of this invention is cut with an ion beam. Therefore, slits extending in the same direction without breaks or with occasional breaks in the middle are assumed to be a complete slit. Breaks are as follows: Figure 2 As shown in the right figure.

[0071] In some alternative embodiments, manganese tetroxide is doped with at least one of the following conditions:

[0072] (1) The seam that communicates with the surface of the secondary particles is a straight seam or a near-straight seam;

[0073] The above-mentioned straight seam refers to a seam that extends in the same direction without any breaks, or a straight seam that extends in the same direction but has occasional breaks in the middle; a quasi-straight seam is a relatively straight seam, and the length of the quasi-straight seam does not exceed 1.1 times the straight distance between the two ends of the quasi-straight seam.

[0074] The channels provided by the aforementioned slits help shorten the distance that the electrolyte needs to penetrate into the core, further improving the electron conduction rate and increasing the charge and discharge capacity.

[0075] (2) The secondary particle includes a core and a shell covering the core, and the seam communicating with the surface of the secondary particle is located in the shell of the secondary particle.

[0076] (3) The secondary particle surface includes a plurality of holes and / or slits communicating with the secondary particle surface.

[0077] In some alternative embodiments, manganese tetroxide is doped with at least one of the following conditions:

[0078] (1) In the secondary particle section, multiple slits intersect; optionally, the multiple slits are arranged in a dendritic pattern in the secondary particle section;

[0079] (2) The maximum length of the slit on the surface of the secondary particles is >0.6μm;

[0080] The maximum length of the seam is the longest straight-line distance between the two ends of the seam;

[0081] Optionally, the maximum length of the slit on the surface of the secondary particles can be any value greater than 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.5 μm, 3.0 μm, or 0.6 μm.

[0082] The longer the maximum length of the aforementioned slit, the more favorable it is for the penetration and diffusion of the electrolyte;

[0083] (3) The ratio of the maximum depth of the slit in the secondary particle section to the diameter of the secondary particle is >10%;

[0084] The aforementioned diameter refers to the longest straight-line distance between two points on the edge of a secondary particle;

[0085] Optionally, the ratio of the maximum slit depth of the secondary particle cut surface to the diameter of the secondary particle can be any value greater than 10%, greater than 12%, greater than 14%, greater than 16%, greater than 18%, greater than 20%, greater than 25%, greater than 30%, greater than 35%, or greater than 10%.

[0086] The greater the maximum depth of the aforementioned slits, the more favorable it is for the electrolyte to penetrate and diffuse.

[0087] In some alternative embodiments, the secondary particle includes a core and a shell covering the core, and satisfies at least one of the following conditions:

[0088] (1) The core porosity is less than the outer shell porosity;

[0089] (2) The diameter of the core is 6-10 μm; the thickness of the outer shell is 0.5-4 μm;

[0090] Optionally, the diameter of the manganese tetroxide-doped core can be any value between 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, or 6-10μm; the thickness of the manganese tetroxide-doped shell can be any value between 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, or 0.5-4μm.

[0091] (3) The overall porosity of manganese tetroxide doped with manganese tetroxide is 10-30%.

[0092] Optionally, the overall porosity can be any value between 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or 10-30%.

[0093] The doped manganese tetroxide prepared in this application has a large core and a small shell. The primary particles in the core are densely arranged, which makes them less prone to collapse during sintering and maintains the overall stability of the secondary particles. The outer shell has pores and slits with special morphology, which is conducive to the penetration of electrolyte, improves electron conduction rate, and improves capacity performance.

[0094] In some optional embodiments, manganese tetroxide satisfies at least one of the following conditions:

[0095] a. The particle size D50 of the doped manganese tetroxide is 8μm-15μm;

[0096] Optionally, the particle size D50 can be any value between 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or 8μm-15μm;

[0097] b. The particle size distribution of doped manganese tetroxide, Span = (D90 - D10) / D50, is 0.35-0.65;

[0098] Optionally, the particle size distribution Span = (D90 - D10) / D50 can be any value between 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65 or 0.35-0.65;

[0099] c. The specific surface area of ​​manganese tetroxide doped with manganese tetroxide is 1-3 m². 2 / g;

[0100] Optionally, the specific surface area can be 1.0 m². 2 / g, 1.5m 2 / g, 2.0m 2 / g, 2.5m2 / g, 3.0m 2 / g or 1-3m 2 Any value between / g;

[0101] d. The tap density of manganese tetroxide doped with manganese tetroxide is 2.4-2.8 g / cm³. 3 ;

[0102] Optionally, the tap density of the manganese tetroxide doped material can be 2.4 g / cm³. 3 2.5g / cm 3 2.6g / cm 3 2.7g / cm 3 2.8g / cm 3 Or 2.4-2.8 g / cm³ 3 Any value;

[0103] e. The molecular formula of manganese tetroxide doped with manganese is Mn 3-x M x O4, where 0 < x ≤ 0.3, and M is Al;

[0104] Optionally, x in the molecular formula can be any value between 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, or 0 < x ≤ 0.3;

[0105] f. The molecular formula of manganese tetroxide doped with manganese is Mn 3-x M x O4, where 0 < x ≤ 0.3, M includes Al, and M also includes one or more of B, Ni, Mg, Ti, Zr, and La.

[0106] A second aspect of this application also provides a method for preparing doped manganese tetroxide, comprising:

[0107] A mixed salt solution containing manganese and dopant elements, a precipitant, a complexing agent, and an oxidant are introduced into the bottom liquid of the reactor to carry out a coprecipitation reaction. The pH value, temperature, and stirring speed are controlled during the coprecipitation reaction. After the coprecipitation reaction is completed, manganese tetroxide is obtained. The complexing agent is an ammonium salt or ammonia water.

[0108] During the coprecipitation reaction, ammonia and ammonium sulfate are used as complexing agents, which can give the secondary particles of the prepared precursor product a special morphology of straight or near-straight seams on the surface and shell, which is conducive to electrolyte penetration and improves capacity performance.

[0109] In some optional embodiments, the preparation method satisfies at least one of the following conditions:

[0110] A. The mixed salt solution includes soluble manganese salt and soluble dopant source;

[0111] B. The soluble manganese salt is selected from one or more of MnCl2, MnSO4, and MnNO3, and the concentration of manganese ions in the soluble manganese salt is 1 to 5 mol / L;

[0112] Optionally, the manganese ion concentration can be 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L or any value between 1 and 5 mol / L;

[0113] C. The dopant elements in the soluble dopant source include one or more of Al, B, Ni, Mg, Ti, Zr, and La. The soluble dopant source is selected from one or more of sulfate, chloride, nitrate, boric acid, and borate. The sum of the concentrations of each dopant element ion in the mixed salt solution is 0.02–0.2 mol / L.

[0114] Optionally, the sum of the concentrations of all dopant ions can be 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.11 mol / L, 0.12 mol / L, 0.13 mol / L, 0.14 mol / L, 0.15 mol / L, 0.16 mol / L, 0.17 mol / L, 0.18 mol / L, 0.19 mol / L, 0.2 mol / L, or any value between 0.02 and 0.2 mol / L.

[0115] D. The base solution includes one or more of the following: pure water, ammonia water, and sodium hydroxide solution;

[0116] E. The precipitant is a sodium hydroxide solution with a mass concentration of 10% to 35%;

[0117] Optionally, the mass concentration of the sodium hydroxide solution can be any value between 10%, 12%, 13%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, or 10% to 35%.

[0118] F. The complexing agent is one or more of ammonium sulfate, ammonia, ammonium nitrate, and ammonium chloride;

[0119] G. The oxidant is one or more of hydrogen peroxide, compressed air, ozone, oxygen, sodium hypochlorite, ammonium persulfate, and sodium thiosulfate.

[0120] In some optional embodiments, the preparation method satisfies at least one of the following conditions:

[0121] 1) Control the pH during the coprecipitation reaction to be 8.0–10.0;

[0122] Optionally, the pH during the coprecipitation reaction can be any value between 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0, or 8.0 to 10.0.

[0123] 2) Control the concentration of the complexing agent during the coprecipitation reaction to 0.5-8 g / L;

[0124] Optionally, the concentration of the complexing agent can be 0.5 g / L, 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L or any value between 0.5 and 8 g / L;

[0125] 3) Control the temperature during the coprecipitation reaction to 40–80℃;

[0126] Optionally, the temperature during the coprecipitation reaction can be any value between 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃ or 40℃ to 80℃.

[0127] 4) Control the stirring speed during the coprecipitation reaction to 400–800 rpm;

[0128] Optionally, the stirring speed can be 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm or any value between 400 and 800rpm;

[0129] 5) During the coprecipitation reaction, the feed flow rate of the mixed salt solution is 1.2 to 6% of the usable volume of the reactor. When the oxidant is prepared as an oxidant solution, the feed flow rate of the oxidant solution is controlled to be 0.3 to 6% of the usable volume of the reactor. When the oxidant is a gaseous oxidant, the feed flow rate of the gaseous oxidant is controlled to be 90 to 700% of the usable volume of the reactor.

[0130] Optionally, the feed flow rate of the mixed salt solution during the co-precipitation reaction can be controlled to any value between 1.2% / h, 1.5% / h, 2% / h, 2.5% / h, 3% / h, 3.5% / h, 4% / h, 4.5% / h, 5% / h, 5.5% / h, 6% / h, or 1.2% to 6% / h of the available reactor volume; the feed flow rate of the liquid oxidant can be controlled to be 0.3% / h, 0.5% / h, 0.8% / h, 1% / h, 1.5% / h, 2% / h, or 2.5% / h of the available reactor volume. The feed rate of the gaseous oxidant can be any value between 0.3% and 6% / h, 3.5% / h, 4% / h, 4.5% / h, 5% / h, 5.5% / h, 6% / h, or 0.3% to 6% / h; the feed rate of the gaseous oxidant can be controlled to be any value between 90% / h, 100% / h, 150% / h, 200% / h, 250% / h, 300% / h, 350% / h, 400% / h, 450% / h, 500% / h, 550% / h, 600% / h, 650% / h, or 700% / h of the available volume of the reactor.

[0131] According to another aspect of this application, a cathode material is also provided, which is prepared by sintering the above-mentioned cathode material precursor with a lithium salt. Specifically, the cathode material precursor and the lithium salt are thoroughly ground in a certain proportion until uniformly mixed, and then placed in a tube furnace for sintering in an air atmosphere. After holding at a certain temperature, the mixture is cooled to room temperature with the furnace to obtain the cathode material. The prepared cathode material has good electrochemical performance and thermal stability.

[0132] Electrochemical performance testing was conducted using a button cell battery: The above-mentioned positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry according to a certain ratio and coated onto aluminum foil to form the positive electrode sheet. A lithium metal sheet was used as the negative electrode sheet. The electrolyte was 1 mol / L LiPF6 / EC:DMC:EMC = 1:1:1. The battery casing, positive and negative electrodes, separator, spring contacts, and gaskets were assembled into a button cell battery in a vacuum glove box. Cyclic testing was performed on the assembled button cell battery at a C / 3 rate between 3-4.3V for 30 cycles, where 1C = 250 mAh / g.

[0133] According to another aspect of this application, a lithium-ion battery is also provided, the raw materials of which include the above-mentioned positive electrode material.

[0134] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.

[0135] Example 1

[0136] This embodiment provides a doped manganese tetroxide, with the chemical formula Mn. 2.9 Al 0.1 O4, its preparation process is as follows:

[0137] ① Raw material preparation: Manganese sulfate and aluminum sulfate are used as raw materials to prepare Mn 2+ 2 mol / L, Al 3+ The solutions are a 0.06 mol / L mixed salt solution, a 10 g / L ammonium sulfate solution, and a 15% sodium hydroxide solution.

[0138] ② Coprecipitation reaction: Deionized water is added to the reactor as the base liquid, the temperature is raised to 70℃, and stirring is started at 800 rpm. At the same time, a mixed salt solution, oxidant, sodium hydroxide solution, and ammonium sulfate solution are added. The flow rate of the mixed salt solution is controlled at 3.3-3.6% / h of the usable volume of the reactor, and the flow rate of compressed air is controlled at 450-520% / h of the usable volume of the reactor. The pH value in the coprecipitation reaction is controlled at 9.3-9.6 by the flow rate of the sodium hydroxide solution; the concentration of ammonium sulfate in the coprecipitation reaction is controlled at 1.5-2.5 g / L by the flow rate of the ammonium sulfate solution. After 15 h of coprecipitation reaction, manganese tetroxide slurry is obtained.

[0139] ③ Use deionized water to wash and filter to obtain the washing product;

[0140] ④ Place the washed product in a regular drying oven and dry it at 90°C for 12 hours to obtain the dried product; after sieving, the manganese tetroxide-doped precursor is obtained.

[0141] The particle size of the finished product was measured using a particle size analyzer, as shown in the table below (the same applies below).

[0142] The surface and cross-sectional morphology of the finished product were examined using scanning electron microscopy, and the results are as follows: Figure 1 , Figure 2 As shown; the surface morphology of the sintered cathode material was inspected, and the results are as follows. Figure 3 As shown.

[0143] Example 2

[0144] This embodiment provides a doped manganese tetroxide, with the chemical formula Mn. 2.82 Al 0.18 O4, its preparation process is as follows:

[0145] ① Raw material preparation: Manganese sulfate and aluminum sulfate are used as raw materials to prepare Mn 2+ 2 mol / L, Al 3+The solutions are a 0.12 mol / L mixed salt solution, a 20% ammonia solution, and an 18% sodium hydroxide solution.

[0146] ② Coprecipitation reaction: Deionized water is added to the reactor as the base liquid, stirring is started, sodium hydroxide solution is added to adjust the pH of the base liquid to 10.0, the temperature is raised to 80℃, and mixed salt solution, oxygen, sodium hydroxide solution and ammonia solution are added simultaneously while stirring at 600 rpm. The flow rate of mixed salt is controlled at 3.4-3.6% / h of the usable volume of the reactor, and the flow rate of oxygen is controlled at 95-105% / h of the usable volume of the reactor. The pH value of the coprecipitation reaction is controlled at 8.3-8.6 by sodium hydroxide solution; the ammonia concentration of the coprecipitation reaction is controlled at 3.5-4.5 g / L by ammonia solution. After the coprecipitation reaction is carried out for 30 h, manganese tetroxide slurry is obtained.

[0147] ③ Use deionized water to wash and filter to obtain the washing product;

[0148] ④ Place the washed product in a regular drying oven and dry it at 90°C for 12 hours to obtain the dried product; after sieving, the manganese tetroxide-doped precursor is obtained.

[0149] The surface morphology of the finished product was inspected using a scanning electron microscope, and the results are as follows: Figure 4 .

[0150] Example 3

[0151] This embodiment provides a doped manganese tetroxide, with the chemical formula Mn. 2.865 Al 0.075 Mg 0.03 B 0.03 O4, its preparation process is as follows:

[0152] ① Raw material preparation: Manganese sulfate, aluminum sulfate, magnesium sulfate, and sodium tetraborate are used as raw materials to prepare Mn 2+ 1.8 mol / L, Al 3+ 0.048 mol / L, Mg 2+ 0.02 mol / L, B 3+ Prepare a 15 g / L ammonium sulfate solution and a 12% sodium hydroxide solution from a 0.02 mol / L mixed salt solution.

[0153] ② Coprecipitation reaction: Deionized water is added to the reactor as the base liquid, stirring is started, sodium hydroxide solution is added to adjust the pH of the base liquid to 10.0, the temperature is raised to 80℃, and mixed salt solution, compressed air, sodium hydroxide solution and ammonium sulfate solution are added simultaneously while stirring at 700 rpm. The flow rate of mixed salt solution is controlled at 3.2-3.4% / h of the usable volume of the reactor, and the flow rate of compressed air is controlled at 450-480% / h of the usable volume of the reactor. The pH value of the coprecipitation reaction is controlled at 8.9-9.2 by sodium hydroxide solution; the concentration of ammonium sulfate in the coprecipitation reaction is controlled at 0.5-1.5 g / L. After the coprecipitation reaction is carried out for 16 h, manganese tetroxide slurry is obtained.

[0154] ③ Use deionized water to wash and filter to obtain the washing product;

[0155] ④ Place the washed product in a regular drying oven and dry it at 90°C for 12 hours to obtain the dried product; after sieving, the manganese tetroxide-doped precursor is obtained.

[0156] The surface and cross-sectional morphology of the finished product were examined using scanning electron microscopy, and the results are as follows: Figure 5 , Figure 6 As shown.

[0157] Example 4

[0158] This embodiment provides a doped manganese tetroxide, with the chemical formula Mn. 2.88 Al 0.075 Ni 0.015 B 0.03 O4, its preparation process is as follows:

[0159] ① Raw material preparation: Manganese sulfate, aluminum sulfate, nickel sulfate, and boric acid are used as raw materials to prepare Mn 2+ 2.1 mol / L, Al 3+ 0.055 mol / L Ni 2+ 0.011 mol / L, B 3+ Prepare a 0.022 mol / L mixed salt solution, a 30 g / L ammonium sulfate solution, and a 15% sodium hydroxide solution;

[0160] ② Coprecipitation reaction: Deionized water is added to the reactor as the base liquid, stirring is started, sodium hydroxide solution is added to adjust the pH of the base liquid to 9.5, the temperature is raised to 75℃, and while stirring at 750 rpm, a mixed salt solution, sodium hydroxide solution, ammonium sulfate solution, and ammonium persulfate solution are added simultaneously. The flow rate of the mixed metal salt is controlled at 3.0-3.2% / h of the usable volume of the reactor, and the flow rate of the ammonium persulfate is controlled at 0.5-0.8% / h of the usable volume of the reactor. The pH value of the coprecipitation reaction is controlled at 8.3-8.5 by the sodium hydroxide solution; the concentration of ammonium sulfate in the coprecipitation reaction is controlled at 1.2-1.8 g / L. After the coprecipitation reaction is carried out for 20 h, manganese tetroxide slurry is obtained.

[0161] ③ Use deionized water to wash and filter to obtain the washing product;

[0162] ④ Place the washed product in a regular drying oven and dry it at 90°C for 12 hours to obtain the dried product; after sieving, the manganese tetroxide-doped precursor is obtained.

[0163] The surface morphology of the finished product was inspected using a scanning electron microscope, and the results are as follows: Figure 7 As shown.

[0164] Comparative Example 1

[0165] Based on Example 1, the raw material was changed to manganese sulfate to prepare Mn 2+ A 2 mol / L manganese sulfate solution was used; with other conditions remaining unchanged, the precursor product was obtained.

[0166] The surface and cross-sectional morphology of the finished product were examined using scanning electron microscopy, and the results are as follows: Figure 8 , 9 As shown.

[0167] Comparative Example 2

[0168] Based on Example 1, the complexing agent was changed to citric acid solution; the reaction temperature was adjusted to 60°C, the feed flow rate of the mixed salt solution was adjusted to 0.5-6% / h of the usable volume of the reactor, the concentration of the complexing agent was controlled to be 0.5-1.5 g / L by citric acid solution, and the co-precipitation reaction was carried out for 20 h with other conditions unchanged to obtain the precursor product;

[0169] The surface and cross-sectional morphology of the finished product were examined using scanning electron microscopy, and the results are as follows: Figure 10 , Figure 11 As shown.

[0170] Comparative Example 3

[0171] Based on Example 2, the complexing agent was changed to sodium citrate solution, and sodium hydroxide solution was added to adjust the pH of the reaction substrate to 10.0. The feed flow rate of the mixed salt solution was adjusted to 1.7-1.9% / h of the usable volume of the reactor. The concentration of the complexing agent was controlled to be 1.5-2.5 g / L by sodium citrate solution. The co-precipitation reaction was carried out for 42 h, and the other conditions remained unchanged to obtain the precursor product.

[0172] The surface morphology of the finished product was inspected using a scanning electron microscope, and the results are as follows: Figure 12 As shown.

[0173] Comparative Example 4

[0174] Based on Example 3, the complexing agent was changed to sodium citrate solution, and sodium hydroxide solution was added to adjust the pH of the reaction substrate to 10.0. The feed flow rate of the mixed salt solution was adjusted to 1.7-1.9% / h of the usable volume of the reactor. The concentration of the complexing agent was controlled to be 1.5-2.5 g / L by sodium citrate solution. The co-precipitation reaction was carried out for 42 h, and the other conditions remained unchanged to obtain the precursor product.

[0175] The surface and cross-sectional morphology of the finished product were examined using scanning electron microscopy, and the results are as follows: Figure 13 , Figure 14 As shown.

[0176] The precursor cross-sectional morphology and data test results of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 1.

[0177] Table 1. Morphology and data of precursor cross sections

[0178]

[0179] Note 1: The seam diameter ratio is the ratio of the maximum depth of the straight or near-straight seam of the secondary particle cross section to the diameter of the secondary particle.

[0180] The test results of the physicochemical parameters of the precursors of Examples 1-4 and Comparative Examples 1-4 are shown in Table 2.

[0181] Table 2 Physicochemical parameters of precursors

[0182] Example 1 <![CDATA[Mn 2.9 Al 0.1 O4]]> 9.68 0.39 1.49 2.54 Example 2 <![CDATA[Mn 2.82 Al 0.18 O4]]> 10.16 0.53 2.54 2.68 Example 3 <![CDATA[Mn 2.865 Al 0.075 Mg 0.03 B 0.03 O4]]> 10.13 0.49 2.49 2.58 Example 4 <![CDATA[Mn 2.88 Al 0.075 In 0.015 B 0.03 O4]]> 10.17 0.52 2.85 2.52 Comparative Example 1 <![CDATA[Mn3O4]]> 10.23 0.37 0.81 2.69 Comparative Example 2 <![CDATA[Mn 2.9 Al 0.1 O4]]> 10.35 0.49 1.89 2.57 Comparative Example 3 <![CDATA[Mn 2.82 Al 0.18 O4]]> 10.14 0.71 0.94 2.59 Comparative Example 4 <![CDATA[Mn 2.865 Al 0.075 Mg 0.03 B 0.03 O4]]> 10.25 0.49 0.92 2.6

[0183] The test results of the precursor electrochemical performance parameters of Examples 1-4 and Comparative Examples 1-4 are shown in Table 3.

[0184] Table 3 Electrochemical performance parameters

[0185] Example 1 127.7 97.64 Example 2 126.1 97.71 Example 3 126.9 97.69 Example 4 127.2 97.64 Comparative Example 1 114.6 95.13 Comparative Example 2 123.8 97.71 Comparative Example 3 123.1 97.78 Comparative Example 4 123.5 97.75

[0186] Batteries using the cathode materials prepared from the precursors of Examples 1-4 and Comparative Examples 1-4 were subjected to cycle tests on assembled coin cells at a C / 3 rate between 3.0 and 4.3 V. The test results are shown below. Figure 15 As shown.

[0187] As can be seen from Examples 1-4, the aluminum-doped manganese tetroxide precursor and the surface of the multi-element doped manganese tetroxide secondary spheres based on the present invention both have special straight seam or near-straight seam structures. The sintered cathode material inherits the precursor structure and has good capacity performance.

[0188] Compared to Examples 1-4, the product prepared in Comparative Example 1 is pure manganese tetroxide without any other elements. The cross-sectional view shows a solid structure, and the surface does not show the special morphology of the present invention. The sintered cathode material exhibits poor capacity and cycle performance. The reasons may be: ① The structure of the undoped product is relatively less stable, resulting in a decrease in cycle performance; ② The product is a solid structure, making it difficult for the electrolyte to penetrate, which affects the capacity.

[0189] Compared to Examples 1-4, the products prepared in Comparative Examples 2-4 are manganese tetroxide-doped precursors, showing a solid structure in cross-section and lacking the special morphology of this invention. This indicates poor capacity of the sintered cathode material. The reason for this may be that the solid structure makes electrolyte penetration difficult, affecting capacity performance. In contrast, Comparative Examples 2 and 3 have similar capacities. This may be because although the products have a wide particle size distribution and high tap density, resulting in a higher volumetric energy density of the sintered cathode material, which can improve capacity performance, aluminum doping does not contribute to increased capacity. In Comparative Example 3, increased aluminum doping may lead to a decrease in capacity. Under these combined effects, the capacities of Comparative Examples 2 and 3 are not significantly different.

[0190] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

[0191] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. In the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

Claims

1. A manganese tetroxide-doped compound, characterized in that, The doped manganese tetroxide includes secondary particles composed of multiple primary particles, and the doped manganese tetroxide secondary particles include multiple slits communicating with the surface of the secondary particles; The secondary particle includes a core and a shell covering the core, with a slit communicating with the surface of the secondary particle located in the shell of the secondary particle.

2. The doped manganese tetroxide according to claim 1, characterized in that, The doped manganese tetroxide satisfies at least one of the following conditions: (1) The seam communicating with the surface of the secondary particles is a straight seam or a near-straight seam; (2) The secondary particle surface includes a plurality of holes and / or slits communicating with the secondary particle surface.

3. The doped manganese tetroxide according to claim 1, characterized in that, At least one of the following conditions must be met: (1) In the secondary particle cross section, multiple slits intersect; (2) The maximum length of the slit on the surface of the secondary particles is >0.6 μm; (3) The ratio of the maximum depth of the slit in the secondary particle cut surface to the diameter of the secondary particle is >10%.

4. The doped manganese tetroxide according to claim 3, characterized in that, The multiple sutures are arranged in a dendritic pattern in the secondary particle section.

5. The doped manganese tetroxide according to claim 1, characterized in that, The secondary particle comprises a core and a shell covering the core, and satisfies at least one of the following conditions: (1) The core porosity is less than the outer shell porosity; (2) The diameter of the core is 6-10 μm; the thickness of the outer shell is 0.5-4 μm; (3) The overall porosity of the doped manganese tetroxide is 10-30%.

6. The doped manganese tetroxide according to any one of claims 1 to 5, characterized in that, The doped manganese tetroxide satisfies at least one of the following conditions: a. The particle size D50 of the doped manganese tetroxide is 8 μm - 15 μm; b. The particle size distribution of the doped manganese tetroxide, Span = (D90 - D10) / D50, is 0.35-0.65; c. The specific surface area of ​​the doped manganese tetroxide is 1-3 m². 2 / g; d. The tap density of the doped manganese tetroxide is 2.4-3.0 g / cm³. 3 ; e. The molecular formula of the doped manganese tetroxide is Mn 3-x M x O4, where 0 < x ≤ 0.3, and M is Al; f. The molecular formula of the doped manganese tetroxide is Mn 3-x M x O4, where 0 < x ≤ 0.3, M includes Al, and M also includes one or more of B, Ni, Mg, Ti, Zr, and La.

7. A method for preparing doped manganese tetroxide according to any one of claims 1 to 6, characterized in that, include: A mixed salt solution containing manganese and dopant elements, a precipitant, a complexing agent, and an oxidant are introduced into the bottom liquid of a reaction vessel to carry out a coprecipitation reaction. The pH value, temperature, and stirring speed are controlled during the coprecipitation reaction. After the coprecipitation reaction is completed, manganese tetroxide is obtained. The complexing agent is an ammonium salt or ammonia water. The mixed salt solution includes a soluble manganese salt and a soluble dopant element source; The pH value is controlled to be 8.0~10.0 during the coprecipitation reaction; The temperature is controlled at 40~80℃ during the coprecipitation reaction. The stirring speed during the coprecipitation reaction is controlled at 400~800 rpm.

8. The method for preparing doped manganese tetroxide according to claim 7, characterized in that, The preparation method satisfies at least one of the following conditions: B. The soluble manganese salt is selected from one or more of MnCl2, MnSO4, and MnNO3, and the concentration of manganese ions in the soluble manganese salt is 1~5 mol / L; C. The doping element in the soluble doping element source includes one or more of Al, B, Ni, Mg, Ti, Zr, and La, and the soluble doping element source is selected from one or more of sulfate, chloride, nitrate, boric acid, and borate. The sum of the concentrations of each doping element ion in the mixed salt solution is 0.02~0.2 mol / L. D. The base liquid includes one or more of pure water, ammonia water, and sodium hydroxide solution; E. The precipitant is a sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is 10%~35%; F. The complexing agent is one or more of ammonium sulfate, ammonia, ammonium nitrate, and ammonium chloride; G. The oxidant is one or more of hydrogen peroxide, compressed air, ozone, oxygen, sodium hypochlorite, ammonium persulfate, and sodium thiosulfate.

9. The method for preparing doped manganese tetroxide according to claim 7 or 8, characterized in that, The preparation method satisfies at least one of the following conditions: 2) The concentration of the complexing agent during the co-precipitation reaction is controlled to be 0.5-8 g / L; 5) During the co-precipitation reaction, the feed flow rate of the mixed salt solution is controlled to be 1.2~6% / h of the usable volume of the reactor; when the oxidant is prepared as an oxidant solution, the feed flow rate of the oxidant solution is controlled to be 0.3~6% / h of the usable volume of the reactor; when the oxidant is a gaseous oxidant, the feed flow rate of the gaseous oxidant is controlled to be 90~700% / h of the usable volume of the reactor.

10. A positive electrode material, characterized in that, This includes cathode materials prepared from doped manganese tetroxide as described in any one of claims 1 to 6.

11. A lithium-ion battery, characterized in that, Includes the cathode material as described in claim 10.

Citation Information

Patent Citations

  • Spherical aluminum-doped manganous-manganic oxide and preparation method thereof

    CN102544472A

  • Manganese tetratrioxide and method for manufacturing the same

    JP2001354425A